Estudo do estrato regenerativo em trechos de floresta estacional semidecidual, no sudeste do Brasil - Corrêa, Laine Silveira (Universidade Federal de São Carlos, 2011)
Was carried out the phytosociological survey of understory of remaining semideciduous forest located at Federal of São Carlos University campus Sorocaba, São Paulo State, Brazil. The goal of this study was to analyze the structural and floristic composition of the understory. Were identified 129 species from 41 botanical families, of these four threatened species and four exotic species. The species were identified in ecological groups as pioneer species (P) and non-pioneer species or latter species (NP), and as canopy species (D) and understory species (S). The families with highest importance value (VI) were Myrtaceae, Euphorbiaceae, Fabaceae, Sapindaceae e Meliaceae, and the species were Actinostemon concepcionis (Chodat & Hassl.) Hochr, Mollinedia clavigera Tul., Eugenia pluriflora DC, Cupania vernalis Cambess., Protium heptaphyllum (Aubl.) Marchand, Trichilia elegans A. Juss., Piper amalago L., Enterolobium contorstisiliquum (Vell.) Morong, Endlicheria paniculata (Spreng.) J.F. Macbr, Matayba elaegnoides Radlk. From the total species collected (129), 77 are canopy species, 29 understory species, and 19 were not identified. As for the ecological groups, 41 species were identified as P, 65 species as NP and 19 were not identified. Among the 77 species of canopy, 38 were collected in previous study on the composition of the canopy. The results attest that in the future, the composition of the canopy will be partially changed, with the possibility of bigger richness, and with more NP species proportion. The results permits to say that these small remaining of semideciduous forest are in intermediate sucessional stage and are important to biodiversity regional conservation.
Keywords: Manejo florestal; Ecologia florestal; Fitossociologia; Ecological succession; Fragmented forests; Understory; Natural regeneration; CIENCIAS BIOLOGICAS::ECOLOGIA